Periorbital Necrotizing Fasciitis in Lung Adenocarcinoma Patient Receiving Afatinib: A Case Report - Kusumawardani, Ida Ayu Jasminarti Dwi; Tan, Leviani; Indraswari, Putu Gita; Yuliawati, Putu; Wiradana, A.A. Gde Agung Anom Arie (Indonesian Journal of Cancer, 2026)
Background: Afatinib is a second-generation Tyrosine Kinase Inhibitor (TKI) approved by the Food and Drug Administration (FDA) as first-line therapy for advanced Non-small cell lung cancer (NSCLC) with distant organ metastasis. However, afatinib has been reported to cause several side effects. Here, we report a case of periorbital necrotizing fasciitis, potentially associated with afatinib use, presenting as a grade 3 side effect in a 59-year-old woman with stage IVB lung adenocarcinoma. This is the first literature reporting afatinib-related periorbital necrotizing fasciitis, a rare sight-threatening infection.Case Presentation: A 59-year-old female patient came to the Emergency Room with a protruding left eye, which is accompanied by redness, purulent discharge, and a blackish wound around the left eye area for the last 5 days. The patient had been diagnosed with stage IVB lung adenocarcinoma (T4N3M1c) six months ago. Previously, she underwent chemotherapy with a combination of Gemcitabine and Carboplatin. The patient then underwent 20 cycles of radiotherapy followed by immunotherapy using afatinib. The patient was then admitted with suspected necrotizing fasciitis of the left periorbital area due to side effects of afatinib. She was given ceftriaxone 2 grams every 24 hours intravenously (IV), analgesics IV, methylprednisolone IV, gentamicin eye drops, and regular wound care. After several days of treatment, the patient had significant improvement. Afatinib therapy was temporarily stopped. Re-evaluation at one month showed significant improvement in the patient's left periorbital area. Afatinib therapy was then continued at a lower dose of 30 mg every 24 hours.Conclusions: Good education and caution are still needed for patients who were given afatinib. More studies on the side effects of afatinib are needed to identify predisposing factors and establish a consensus on the management of afatinib-induced periorbital necrotizing fasciitis in NSCLC patients.